AB0691 Arterial APS (AAPS): clinical and laboratory findings in a cohort of 28 patients. (23rd January 2014) - Kuzenko, A.; Sosso, L.; Montaruli, B.; Rovere, M.E.; Castagno, I.; Crema, F.; Napolitano, E.; Silvestro, E.; Bonzano, A.; Sciascia, S.; Bertero, M.T.
Abstract : Background: To our knowledge the most complete study of vascular manifestations of APS was published in 2002 (1), using the Sapporo criteria. There are no recent papers on arterial manifestations of APS using the Miyakis 2006 criteria (2). High risk of recurrence is reported in triple positivity for aPL. (3). Objectives: To evaluate immunological, neurological, cardiological and laboratory findings in patients with aAPS. Methods: Multidisciplinary evaluation of 28 consecutive patients diagnosed with APS (Miyakis criteria), with at least one arterial manifestation proved with imaging studies. Results: 19 women and 9 men (mean age 45, range 27-70) were diagnosed with APS according to Miyakis criteria, with total of 43 vascular events. 9 of them had isolated APS, 12 associated with SLE/UCTD and 7 with other autoimmune diseases. Clinical and laboratory features are shown in the following Table: All patients presented cardiovascular risk factors (smoking, arterial hypertension, hypercolesterolemia, obesity, family history for Coronary Artery Disease), more factors being present in male patients. Thrombophilia study resulted negative in 18, positive for heterozygosity of the factor II in 3, hyperhomocysteinemia in 1 and elevated factor VIII level in 1 case. The neurological evaluation revealed 17 cases of headache, 8 of depression, 7 of cognitive deficit and 3 of seizures. Livedo reticularis was present in 8 patients, all with cerebrovascular events and alterations in magnetic resonance imaging. The echocardiographic study revealed preserved ejection fraction (60-70%) in all cases. Females presented severe valvulopathies in 2, moderate mitralic regurgitation in 3 and mild aortic and mitralic regurgitation in 2 cases. Pulmonary artery pressure was elevated in 2 (45 and 49 mm Hg) and the diastolic function was altered in 2 patients. Male patients showed signs of accelerated atherosclerosis. 3 female patients had both vascular and obstetric morbidity; 16 with only vascular manifestations had uneventful pregnancies with good neonatal outcome. Conclusions: Stroke is the most frequent arterial event in APS. All aAPS patients present cardiovascular risk factors. Ecocardiographic study is advisable in aAPS patients in order to exclude silent valvulopathies. Recurrences correlate with triple antiphospholipid positivity.Female aAPS patients do not seem to experience pregnancy morbidity. References: Miyakis et al. J Thromb Haemost 2006;4:295-306. Cervera et al. Arthritis Rheum 2002;46:1019-27. Pengo et al. J Thromb Haemost 2010;8:237-42 Disclosure of Interest: None Declared